Regional tree-ring oxygen isotope deduced summer monsoon drought variability for Kumaun-Gharwal Himalaya. (1st February 2023) - Shah, Santosh K.; Berkelhammer, Max; Li, Qiang; Mehrotra, Nivedita; Thomte, Lamginsang; Shell, Richard; Pandey, Uttam; Gaire, Narayan P.; Kathayat, Gayatri; Sinha, Ashish
Abstract: The precipitation in the Kumaun-Gharwal (Uttarakhand) Himalaya (KGH) is predominantly regulated by the Indian summer monsoon (ISM) and has been declining over the last century. However, because of limited historical data, it is difficult to place this recent decreasing trend in the context of pre-anthropogenic influences and understand a fuller range of hydroclimate scenarios for the region. Thus, we developed a 508-year regional tree-ring stable oxygen isotope (δ 18 OTR ) record for multiple coniferous taxa ( Abies spectabilis, Cedrus deodara and Picea smithiana) for the KGH, which spanned 1508–2015 CE. The δ 18 OTR record explained 35.8% of instrumental June–August Palmer Drought Severity Index (JJAPDSI ) variance modelled from a nearby meteorological station. The JJAPDSI reconstruction shows regional coherency with both instrumental and proxy-based independent hydroclimatic records providing confidence that it is a reliable proxy to assess the long term hydroclimatic variability of the region. We identified decreasing strength of JJAPDSI reconstruction in KGH during recent decades indicating intensified drought. This is in the context of pre-anthropogenic influences and understand a fuller range of hydroclimate scenarios for the region. The δ 18 OTR also has coherency with Pacific and Indian Ocean sea surface temperature variability illustrating the broader teleconnections that influence the regional hydroclimate. Highlights: The strength of the Indian Summer monsoon has declined in the high altitude regions of the Kumaun-Gharwal Himalaya (KGH). Tree-ring stable oxygen isotope record (δ 18 OTR) of multiple conifer taxa established a 508-year long regional chronology. JJA PDSI reconstruction was carried out and revealed past droughts in the KGH. These past droughts during the recent decades have similar intensity as the past drought in the early part of the record. The δ 18 OTR regional record has teleconnections with SST in the Pacific and Indian Ocean.